2007
DOI: 10.4161/cc.6.8.4103
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of p53 in the Dynamics of Cell Cycle Response to DNA Damage Interpreted by a Mathematical Model

Abstract: AbbreViAtioNs AbstrACtDespite numerous studies on the tumor suppressor p53, a complete picture of its role in cell arrest and killing in G 1 , S and G 2 M phases after drug treatment is lacking. We tackled the analysis of the complexity of cell cycle effects combining the time-course measures with different techniques with the aid of a computer program simulating cell cycle progression. This mixed experimental-simulation approach enabled us to decode the dynamics of the cytostatic and cytotoxic responses to ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Each cell line may use the same bricks to build up the drug response with different strength, or not use one brick at all if the line is defective for important proteins of the associated network. Similar studies with other cell lines have qualitatively confirmed the responses with IGROV1 (5) and revealed the contribution of particular molecular defects in each checkpoint activity (4).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Each cell line may use the same bricks to build up the drug response with different strength, or not use one brick at all if the line is defective for important proteins of the associated network. Similar studies with other cell lines have qualitatively confirmed the responses with IGROV1 (5) and revealed the contribution of particular molecular defects in each checkpoint activity (4).…”
Section: Discussionsupporting
confidence: 68%
“…We applied our modeling approach on the measures taken with different techniques after treatments with five "classic" anticancer drugs, at concentrations spanning the whole range of drug efficacy, and at several times after drug exposure. Specific comments to cell cycle effects of each drug and possible connections to molecular mechanisms of action were discussed in other publications (1)(2)(3)(4)(5). Exploiting the fact that the cell line, the experimental plan, and techniques were the same, we were able to create a database including data on all the drugs together, and we analyzed the results synoptically to extract the general features of the dynamics of G 1 , S, and G 2 -M checkpoint activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several researchers have targeted a variety of dynamical processes within biological systems for their computational analysis ranging from studies into parallel reaction pathways [130], HBV infections [131] and in silico analysis of SarCoV [132]. In terms of DDR signalling pathway, most of systems biology studies have been undertaken to examine and model the oscillatory patterns of DDR protein induction following DNA damage in light of the known biological insights [133][134][135]137] with some reports focussing on elucidating the role of such oscillations in determining cell fate i.e. DNA repair, cell cycle arrest or apoptosis [88,100,103,138].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that at least two pathways regulate apoptosis: one dependent on the tumor suppressor gene P53 and the other P53-independent [11,12].…”
Section: Discussionmentioning
confidence: 99%